2005
DOI: 10.1097/01.tp.0000186957.32801.c0
|View full text |Cite
|
Sign up to set email alerts
|

Mycophenolate Mofetil in Pediatric Renal Transplantation

Abstract: Mycophenolate mofetil (MMF) has become a popular immunosuppressive agent in pediatric renal transplantation and has helped to address the unique challenges of transplantation in this population. This paper reviews the early studies that proved MMF's efficacy in reducing the risk of acute renal rejection, as well as its safety and tolerability in comparison to azathioprine. Key conclusions about the pharmacokinetics of MMF from studies of MMF alone and in combination with other immunosuppressive therapies are o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 49 publications
1
24
0
Order By: Relevance
“…9 Pediatric use MMF has been successfully used in the pediatric population for the prevention of renal transplant rejection. 159 In dermatology, there have been reports of its use, with much lower frequency than that in the adult population. It was reported to be successful in a case of childhood immunoglobulin A (IgA)emediated epidermolysis bullosa acquisita.…”
Section: Pregnancy and Pediatric Use Pregnancymentioning
confidence: 98%
“…9 Pediatric use MMF has been successfully used in the pediatric population for the prevention of renal transplant rejection. 159 In dermatology, there have been reports of its use, with much lower frequency than that in the adult population. It was reported to be successful in a case of childhood immunoglobulin A (IgA)emediated epidermolysis bullosa acquisita.…”
Section: Pregnancy and Pediatric Use Pregnancymentioning
confidence: 98%
“…The first study on MPA pharmacokinetics in pediatric renal allograft recipients showed that MMF dosages of 23 and 30 mg/kg yielded MPA exposure (AUC 0 to 12 hours ) in the same range as derived from adult studies of approximately 30 mg ϫ h/L (91). Closer analysis of the pharmacokinetics indicated that pediatric MMF dosage could be determined more accurately when calculated on the basis of body surface area and that this target could be achieved using a starting dosage of 600 mg/m 2 per dose (1200 mg/m 2 per d) in patients on concomitant CsA therapy (91). This body surface area-related MMF dosing leads to a comparable MPA exposure over the entire pediatric age range (14).…”
Section: Pediatric Transplantationmentioning
confidence: 99%
“…When MMF needs to be reduced or discontinued (in approximately 13 to 16% of pediatric recipients), the reasons are usually gastrointestinal (e.g., nausea, upper abdominal pain, diarrhea) and hematologic (e.g., leucopenia, anemia) (94,95). It was assumed that temporary discontinuation of MMF had no effect on acute rejection; however, this may not be the case, particularly in patients who are treated with a steroid-free reg-imen.…”
Section: Pediatric Transplantationmentioning
confidence: 99%
“…These reported target values are similar in adults and children, although there are conflicting reports on the values of TDM pharmacokinetics parameters in predicting outcome in paediatric patients [4,33,34]. The dose required to obtain MPA AUC within the therapeutic range was investigated in a few paediatric studies that differed in patients' ages, post-transplantation delay and associated immunosuppressants.…”
Section: Discussionmentioning
confidence: 99%
“…It is increasingly prescribed in paediatric renal transplantation, often replacing azathioprine, in combination with a calcineurin inhibitor [4]. Indeed, it reduces the occurrence of acute rejection in comparison with azathioprine and is well tolerated, without nephrotoxicity or cosmetic side effects [5].…”
Section: Introductionmentioning
confidence: 99%